2007
DOI: 10.1007/s10517-007-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans of the trabecular meshwork of the eye in primary juvenile glaucoma

Abstract: Significant changes in the qualitative and quantitative composition of glycosaminoglycans (decreased content of sulfated glycosaminoglycans and increased content of collagen-bound proteoglycanes) in the trabecular meshwork of the eye in primary juvenile glaucoma indicate fibrosis of the juxtacanalicular tissue, which was detected in pathomorphological examination of the operation material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
1
11
0
Order By: Relevance
“…Significant changes in the qualitative and quantitative composition of glycosaminoglycans were detected in PJG presenting as a trend to reduction of the content of sulfated glycosaminoglycans, diffuse proteoglycans, and a significant increase in the content of collagen-bound proteoglycans, indicating collagenogenesis intensification in the juxtacanalicular tissue and deep layers of the sclera [1], which was confirmed by the results of ultrastructural analysis of the operation material.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Significant changes in the qualitative and quantitative composition of glycosaminoglycans were detected in PJG presenting as a trend to reduction of the content of sulfated glycosaminoglycans, diffuse proteoglycans, and a significant increase in the content of collagen-bound proteoglycans, indicating collagenogenesis intensification in the juxtacanalicular tissue and deep layers of the sclera [1], which was confirmed by the results of ultrastructural analysis of the operation material.…”
Section: Resultssupporting
confidence: 61%
“…For example, significant changes in qualitative and quantitative composition of glycosaminoglycans of the trabecular networks of the eye and intervertebral disc were demonstrated in PJG [1,2].…”
mentioning
confidence: 99%
“…It has also been reported that there are elevated concentrations of TGF-β 2 in the aqueous humor of eyes with POAG (59-61) and in developmental glaucoma (61). The trabecular tissue in developmental glaucoma is associated with an abnormal distribution of HS that exhibits an abnormal accumulation (29) or a significant loss (31). These findings may indicate that improper expression of TGF-β 2 and HS can promote the immaturity of the anterior chamber angle in developmental glaucoma or cause impaired cellular function in the trabecular meshwork and Schlemm canal of POAG.…”
Section: Discussionmentioning
confidence: 97%
“…Both the accumulation and changes of the component in the human trabecular meshwork are thought to affect the aqueous outflow resistance. Abnormal expression of glycosaminoglycans and their glycoproteins, along with proteoglycans in the trabecular meshwork, have been found in human glaucoma (29)(30)(31). Heparan sulfate (HS) is a glycosaminoglycan component of the proteoglycans that is expressed in the extracellular matrix of the iridocorneal angle and on cell surfaces of the trabecular meshwork cells (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…This balance is one of the components of PJG pathogenesis, including also genetically determined qualitative and quantitative changes in the connective tissue glycosaminoglycans [3].…”
Section: Resultsmentioning
confidence: 99%